The Impact of Tobacco Control Policies on Smoking Initiation in Europe - Jan C. van Ours; Ali Palali (Tinbergen Institute, 2017)
Our paper investigates the effect of tobacco control policies on smoking initiation in eleven European countries. We analyze longitudinal data of individuals by using information about their age of onset of smoking. We apply hazard rate models to study smoking initiation. Thus, we are able to take into account observed and unobserved personal characteristics as well as the effect of the introduction of a variety of tobacco control policies including bans on tobacco advertisements, smoke-free air regulation, health warnings on packages of cigarettes and treatment programs to help smokers quitting. We find that none of these tobacco control policies influence smoking initiation.
Keywords: I12; C41; 330; tobacco control policies; smoking initiation; hazard rate models